Regulation of ncRNAs involved with ferroptosis in various cancers - Hu, Chenxi; Zeng, Xiangbo; Zhu, Yuanchao; Huang, Zehai; Liu, Jiacheng; Ji, Ding; Zheng, Zaosong; Wang, Qiong; Tan, Wanlong (Frontiers in Genetics, 2023)
As a special pattern of programmed cell death (PCD), ferroptosis is reported to participate in several processes of tumor progression, including regulating proliferation, suppressing apoptotic pathways, increasing metastasis, and acquiring drug resistance. The marked features of ferroptosis are an abnormal intracellular iron metabolism and lipid peroxidation, which are pluralistically modulated by ferroptosis-related molecules and signals, such as iron metabolism, lipid peroxidation, system Xc-, GPX4, ROS production, and Nrf2 signals. Non-coding RNAs (ncRNAs) are a type of functional RNA molecule that is not translated into a protein. Increasingly, studies demonstrate that ncRNAs have a diversity of regulatory roles in ferroptosis, thus influencing the progression of cancers. In this study, we review the fundamental mechanisms and regulation network of ncRNAs on ferroptosis in various tumors, aiming to provide a systematic understanding of recently emerging noncoding RNAs and ferroptosis.